Food Insecurity and Poverty Dynamics among Rural Households in Eastern Sudan: Evidence from the Red Sea State - Abdulrahman, Badreldin Mohamed Ahmed; Sabbil, Adam Ahmed Soliman (International Journal of Economics and Financial Issues, 2025)
This study investigates the relationship between food insecurity and poverty among rural households in Red Sea State, Eastern Sudan. Drawing on a cross-sectional household survey conducted across three localities—Suakin, Port Sudan, and Arbaat—the analysis applies the FAO Food Insecurity Experience Scale (FIES) and chi-square statistical tests to examine how gender, migration status, education, and household size influence welfare outcomes. Based on a field survey of 394 households across Suakin, Port Sudan, and Algonub (Arbaat), the study examines demographic characteristics, income-generating strategies, food insecurity, and poverty prevalence. Results reveal that 47.2% of households experience moderate to severe food insecurity, and 84.5% live living below the international poverty threshold of USD 1.90/day. Disaggregated findings reveal significant disparities: Only 17% of female-headed households are food secure compared to 39.9% of male-headed households, while 94.3% of females live below the poverty line versus 81.7% of males. Migration status further amplifies vulnerability—none of the refugee households were food secure, and 100% live in poverty, compared to 13.8% food security and 93.3% poverty among IDPs, and 37.8% food security and 83.2% poverty among host communities. These insights underscore the importance of gender-sensitive and migration-aware policy interventions to build resilience and reduce poverty in fragile rural contexts.